Improvement of temperature surveillance of neonates in low-resource settings by a simple low-cost device: a descriptive study - Ajib Phiri; Orsolya Genzel-Boroviczeny; Andreas Schultz; Janneke Garvs (BMJ Publishing Group, 2024)
Introduction Neonatal hypothermia in low-resource settings is prevalent and closely associated with high morbidity and mortality. We examined if an easy-to-read temperature detector device improves health outcomes.Methods In a descriptive study, 1009 admissions to a neonatal ward in a tertiary care hospital in Lilongwe, Malawi, were analysed and divided into a baseline and a trial group. The data of 531 newborns with standard care (SC) before the trial were compared with 478 newborns during the implementation of the device (device care=DC). Staff and caregivers were trained on using the device and how to react in case of hypothermia. Data were collected from patient files, device documentation sheets, interviews and focus group discussions. Hypothermia was defined as a body temperature <36.5°C.Results During the trial, body temperatures throughout the hospital stay were significantly more often obtained (p<0.0001). The median temperature measurements per newborn per day were 1.3 times with SC and 1.6 times with DC, and mild hypothermia was more frequently detected. Moderate hypothermia was avoided in the lightest weight group possibly contributing to significantly shorter hospital stays of surviving newborns (p=0.007). Many caregivers had difficulties using and interpreting the device correctly, and 47% of the reported colours did not match the registered temperatures. Contrary to the above, a questionnaire and focus group discussions with caregivers and health workers showed a high acceptance and the overall opinion that the device was beneficial.Conclusion With more frequent temperature checks, infants with lower birth weight possibly benefited from implementing an easy-to-read continuous temperature indicator, but hypothermia rates remained high. Our data and experiences reveal structural, communicational and consistency/interpretation deficits. Although specifically designed for low-resource settings, the implementation of the device needs a well-working and structured environment, especially regarding staff and caregiver communication.